(untitled) (Homoeopathy for All, 2021)
Many communicable diseases which include diarrhoeal diseases are endemic in the country. 1 It is a documented fact that diarrhoeal diseases form major public health problem in children under 5 years of age, especially in developing countries. In India, presently the diarrhoeal morbidity stands at 1.07 million cases and mortality stands at 2040 in these children2 Distinct seasonal patterns of diarrhoea occur in many geographical areas. In temperate climates, bacterial diarrhoea occur more frequently during the warm season, whereas viral diarrhoea, particularly diarrhoea caused by rotavirus peak during the winter. In tropical area, rotavirus diarrhea occurs throughout the year, increasing in frequency during the drier, cool months, whereas bacterial diarrheas peak during the warmer, rainy season. The incidence of persistent diarrhea follows the same seasonal patterns as that of acute watery diarrhea.